The Late Eneolithic Groups from the Dniester-Prut Interfluve: Some Questions of their External Contacts and Chronology - Sîrbu, Ghenadie; Król, Dariusz; Heghea, Serghei (Baltic-Pontic Studies, 2020)
In this article we would like to point out some issues related to a series of ceramic materials found in sites attributed to the Late Enolithic groups of Brînzeni and Gordinești in the Dniester-Prut interfluve. In terms of technology and stylistics in the case of pottery from the Brînzeni type sites and stylistics in the case of pottery from the Gordinești type sites, we can see some analogies in the cultural environment of the central European area. For the Brînzeni group the clearest analogies tend to be seen in eastern, southern and south-eastern areas of the Funnel Beaker culture, whereas for the Gordinești group this seems to be visible within the Złota culture in the Sandomierz Upland, Middle Vistula region. Another issue of our study concerns the chronological frames of these two groups. Analyses of the radiocarbon data series obtained so far allow us to make some careful corrections in the chronological scheme of the Late Eneolithic for eastern Europe. Both mentioned issues fit into socio-cultural relations in the East Carpathian area in the context of the cultural transformations in the second half of the 4th millennium BC.